Translational regulation of mammalian and Drosophila citric acid cycle enzymes via iron-responsive elements. - Gray, Nicola K.; Pantopoulos, Kostas; Dandekar, Thomas; Ackrell, B A; Hentze, Matthias W. (Proceedings of the National Academy of Sciences of the United States of America, 1996)
The posttranscriptional control of iron uptake, storage, and utilization by iron-responsive elements (IREs) and iron regulatory proteins (IRPs) provides a molecular framework for the regulation of iron homeostasis in many animals. We have identified and characterized IREs in the mRNAs for two different mitochondrial citric acid cycle enzymes. Drosophila melanogaster IRP binds to an IRE in the 5' untranslated region of the mRNA encoding the iron-sulfur protein (Ip) subunit of succinate dehydrogenase (SDH). This interaction is developmentally regulated during Drosophila embryogenesis. In a cell-free translation system, recombinant IRP-1 imposes highly specific translational repression on a reporter mRNA bearing the SDH IRE, and the translation of SDH-Ip mRNA is iron regulated in D. melanogaster Schneider cells. In mammals, an IRE was identified in the 5' untranslated regions of mitochondrial aconitase mRNAs from two species. Recombinant IRP-1 represses aconitase synthesis with similar efficiency as ferritin IRE-controlled translation. The interaction between mammalian IRPs and the aconitase IRE is regulated by iron, nitric oxide, and oxidative stress (H2O2), indicating that these three signals can control the expression of mitochondrial aconitase mRNA. Our results identify a regulatory link between energy and iron metabolism in vertebrates and invertebrates, and suggest biological functions for the IRE/IRP regulatory system in addition to the maintenance of iron homeostasis.